Âbideleri ve kitabeleri ile Niğde Aksaray tarihi - Konyalı, İbrahim Hakkı, 1896-1984. (İstanbul İstanbul)
3 c. (1. c. xxiii, 1408 s. ; 2. c. xxiii, [1411]-2744 s. ; 3. c. viii, [2745]-3309 s., [1] s., 2 katlı sayfa plan)